Enchanted night a novella - Millhauser, Steven (Phoenix, 2001)
A fantasy novella on the happenings in a Connecticut town one moonlit night. Two people romance, a woman pines for her lover, teens break into a house, a store mannequin comes to life. By the author of Martin Dressler.